Testing the GDP-energy consumption and GDP-CO2 emissions nexus in selected Asian countries a time series analysis. - Parcon, Nikka Mharie J.
This study aims to determine if there is a long-term relationship between GDP per capita and energy consumption and between GDP per capita and carbon dioxide (CO2) consumption is disaggregated into renewable energy sources namely solar, wind, and hydroelectricity and non-renewable energy sources namely oil, coal, natural gas, and nuclear. The results of this study reveal that oil, natural gas, coal, hydroelectricity, solar energy, and wind energy consumption are not cointegrated with GDP per capita for all countries. All variables of Indonesia, Israel, Japan, Philippines, Saudi Arabi, Singapore, South Korea, Turkey and United Arab Emirates are not cointegrated with GDP per capita. The findings imply that there is no long-term relationship between GDP per capita and other variables in the study. The results also reveal a long-term relationship between GDP per capita and CO2 per capita in Malaysia and Pakistan and GDP per capita and nuclear energy consumption in Pakistan.